2005
DOI: 10.1093/jac/dki105
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression profiling of the response to ciclopirox olamine in Candida albicans

Abstract: Consistent with the hypothesis that ciclopirox olamine acts as an iron chelator, it induced changes in expression of many genes involved in iron uptake. Despite induction of the multidrug efflux pump genes CDR1 and, to a lesser extent, CDR2 by ciclopirox olamine, these genes do not affect susceptibility to this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
7
25
0
Order By: Relevance
“…This response is sim- ilar to that registered for C. albicans treated with ciclopirox olamine, an antifungal drug that acts as an iron chelator, restricting the iron availability to the fungal cell and consequently inhibiting growth (19,28). In our hands, the presence of the chelator ferrozine reduced the C. albicans growth extent in a manner similar to that caused by MAb C7.…”
Section: Discussionsupporting
confidence: 76%
“…This response is sim- ilar to that registered for C. albicans treated with ciclopirox olamine, an antifungal drug that acts as an iron chelator, restricting the iron availability to the fungal cell and consequently inhibiting growth (19,28). In our hands, the presence of the chelator ferrozine reduced the C. albicans growth extent in a manner similar to that caused by MAb C7.…”
Section: Discussionsupporting
confidence: 76%
“…We also note that a previous study reported upregulation of FRE7 in C. neoformans under low-copper conditions (43). Besides metal regulation, transcription of ferric reductase genes in fungal pathogens is also affected by pH, macrophage engulfment, antifungal drugs, and infection, suggesting distinct regulation of different ferric reductases in response to specific environmental conditions (23,(44)(45)(46). These factors remain to be examined in C. neoformans, and more detailed interpretation of expression patterns and reductase activities will also require knowledge of the localization of each enzyme.…”
Section: Discussionmentioning
confidence: 62%
“…Proteomic analysis of cytoplasmic proteins also showed upregulation between sensitive and resistant strains [26]. Expression of ORF19.822 is upregulated in transcription profiling studies in the presence of the drug ciclopirox olamine [27] and in the absence of adenylate cyclase (CYR1) [28] but down regulated when grown on bovine serum albumin in the presence of subinhibitory fluconazole [29]. This appears to be the first verification of this hypothetical protein.…”
Section: Discussionmentioning
confidence: 90%